Tolerance Some Soybean Cultivars to Stress Drought at Vegetative to Generative Phase - Ahmad Riduan; Rainiyati Rainiyati; Yuia Alia; Sosiawan Nusifera (Jurnal Penelitian Pendidikan IPA, 2022)
Soybean is one of crop which many conducting in Jambi province, where this area is one of sentra soybean producer in Indonesia. Main constraint in expansion of soybean in Jambi province is ability of adaptation of low crop to condition of area that is partly are consisted of area of marjinal with level of low fertility , applies strains or cultivar indication by drought tolerance to earn is one of the solutions forplies strains or cultivar indication by drought tolerant to earn is one of alternative of trouble-shooting. Examination of soybean cultivar tolerance to stres drought at vegetative to generative phase (15 - 45 Day After Plants / DAP) done in glasshouse by using Split Plout Design. Treatment of stres drought as main check and soybean cultivar as child of check. From result of observation, treatment of stres dryness at vegetative phase and generative can reduce and pursues growth and result of soybean cultivar tested. But for soybean cultivar Derap-1, Dena-2, Deja-2, Dering-1, Grobogan, Detam-1 and Dega-1, treatment of stres drought exactly causes improvement of root length to range from 7,14 - 60,57%. Based on variable dry weigh seed,seven soybean cultivars tested canot be classified in group of tolerant and tolerant medium to stres drought at vegetative to generative phase that is var. Argo Mulyo, Dena-1, Derap-1, Dena-2, Deja-2, Dering-1, Grobogan dan Detam-1. Stres drought causes improvement can of leaf prthe mechanism of soybean tolerance to stres drought can improve root length as mechanism of tolerance in morphology and or improveprovement of root length as mechanism of tolerance in morphology and or through improvement of proline content as mechanism of tolerance physiologically